2023
DOI: 10.3390/brainsci13030422
|View full text |Cite
|
Sign up to set email alerts
|

Moderate-Intensity Intermittent Training Alters the DNA Methylation Pattern of PDE4D Gene in Hippocampus to Improve the Ability of Spatial Learning and Memory in Aging Rats Reduced by D-Galactose

Abstract: (1) Background: Aging is the main risk factor for most neurodegenerative diseases, and the inhibition of Phosphodiesterase 4(PDE4) is considered a potential target for the treatment of neurological diseases. The purpose of this study was to investigate the inhibitory effect of moderate-intensity intermittent training (MIIT) on PDE4 in the hippocampus of rats with D-galactose (D-gal)-induced cognitive impairment, and the possible mechanism of improving spatial learning and memory. (2) Methods: the aging rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Moreover, since a previous study has shown the role of PDE4 in hippocampal neurogenesis (Li et al 2009 ), we believe that exercise-driven PDE4 methylation will improve learning functions via facilitating both neurogenesis and synaptogenesis. The current results support our findings suggesting a critical role for exercise training in promoting cognitive function by increasing PDE-4 methylation (Zhang et al 2023 ). The current data further broaden our understandings for central effects of exercise, which leads to the neural recovery covering neuronal oxidative stress and synaptic plasticity.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, since a previous study has shown the role of PDE4 in hippocampal neurogenesis (Li et al 2009 ), we believe that exercise-driven PDE4 methylation will improve learning functions via facilitating both neurogenesis and synaptogenesis. The current results support our findings suggesting a critical role for exercise training in promoting cognitive function by increasing PDE-4 methylation (Zhang et al 2023 ). The current data further broaden our understandings for central effects of exercise, which leads to the neural recovery covering neuronal oxidative stress and synaptic plasticity.…”
Section: Discussionsupporting
confidence: 93%
“…In an aging rat model induced by D-galactose, 6-8 weeks of moderate-intensity exercise training improved spatial learning and memory [15,17]. Voluntary exercise mitigated cognitive deficits and suppressed neural degeneration in the hippocampus of senescenceaccelerated SAMP8 mice [18].…”
Section: Discussionmentioning
confidence: 99%
“… 70 After the injection of D-gal, the rats from AE groups were submitted to aerobic intermittent training on a treadmill (Shanghai Xinruan Information Technology Co., Ltd., Shanghai, China) for 5 days per week and continued for 8 weeks. 71 Firstly, the rats performed warm-up exercises for 10 min (intensity: 50%-60% of maximal oxygen uptake (VO 2 max), 10 m/min) on a treadmill under 0° slope condition. Secondly, rats ran for 4 min (intensity: 80%-90% of VO 2 max, 20 m/min) under the same condition.…”
Section: Methodsmentioning
confidence: 99%